SOSIALISASI DAN PENDAMPINGAN BRANDING PRODUK SERTA DIGITAL MARKETING SEBAGAI UPAYA PENGUATAN KAPASITAS UMKM DI MUARA JAWA PESISIR - Darnah Darnah; Meirinda Fauziyah; Raditya Arya Kosasih (Jurnal Abdi Insani, 2025)
Micro, small, and medium enterprises (UMKM) play a vital role in Indonesia's economy. MSMEs have been demonstrated to have a significant impact on employment opportunities and the overall well-being of communities. This community service activity aims to enhance the understanding and skills of UMKM actors in Muara Jawa Pesisir with regard to product branding and the utilization of digital marketing as a marketing strategy. The methodology employed entails the dissemination of knowledge through socialization and mentorship of the Dahlia and KWT Kompetitif UMKM groups. The findings of the activity demonstrate that UMKM actors have obtained a novel comprehension of the significance of brand identity and digital marketing, and are capable of implementing it through straightforward packaging design and promotional strategies. The integration of branding and digital marketing is projected to enhance product image, broaden market reach, and augment the competitiveness of UMKM in the context of technological advancements and intensifying business competition. Consequently, this community service initiative contributes substantially to the sustainability of local UMKM, thereby enabling them to thrive and evolve autonomously.